Tanggung Jawab Produsen di Bidang Pangan Terhadap Konsumen - Dezonda R Pattipawae (Faculty of Law Hang Tuah University, 2017)
Practically consumer protection is one of the legal developments which are part of national development. The key point of the issue of consumer protection is that consumers and producers (product distributor or employers) need each other. Production is meaningless if nobody mengkonsumsikannya and products are consumed safely and satisfactorily, in turn, is free promotion for employers. rule of law is very important in order to protect consumers. In sustaining the economy of consumers occupy an important position, but ironically as one of the economic actors are very weak position of the consumer in terms of legal protection. In Indonesia, consumers who had been in a weak position impression of only being an object businesses promotion tips, as well as the sale of a very expansive way. Weak consumer's position caused partly still low awareness and consumer education in Indonesia.